NORMATIVE ANALYSIS OF EARNINGS PER SHARE REPORTED BY COMPANIES WITH STOCK EXCHANGE - Vilchez Olivares, Percy (2017)
In our country, companies listed on the Lima Stock Exchange adopted the International Financial Reporting Standards since 2011. Within the inventory of available standards, IAS 33 Earnings per Share is an accounting standard related to the presentation and disclosure of the Financial indicator called “earnings per share” that is widely used by investors, to make decisions such as buying or selling equity instruments of entities and evaluate the financial returns of the entity.The goal of this research is to analyze the degree of compliance of mining, industrial and public utility companies listed on the Lima Stock Exchange in the adoption of IFRS with respect to the presentation and accounting disclosure required in IAS 33 Earnings per share for the period 2015. Also, the existence of financial instruments that, at some point in the future, generate potential ordinary shares with respect to the financial structure in the same period. The results show that there is insufficient regulatory compliance, not allowing to have relevant financial information on Earnings per share and there is a very low level of financial instruments that generate potential ordinary shares in the financial structure of companies.